Efficacy of Vibroacoustic Stimulation Treatment of Enuresis in Children - Nikolovski, Srdjan; Fatovic Milicevic, Bozica (Journal of Pediatric Nephrology, 2020)
Background and Aim: Functional voiding disorders (FVDs) are common problems in children. The effect of vibroacoustic therapy has not been examined in children with FVDs. The aim of this study was to investigate the efficacy of vibroacoustic therapy for treatment of FVDs in children. Methods: Seventy-eight children were included in this prospective study. Dysfunctional voiding score (DVS) and nocturnal enuresis (NE) score were measured before and after vibroacoustic treatment. The success of vibroacoustic therapy use was evaluated according to the percentage of decrease in DVS and NE scores relative to the pre-treatment values. Descriptive and analytic statistical methods were applied for data analysis using SPSS software version 22.0. Results: The mean age of the participants was 8.65±3.11 years, and half of them were boys. Of 78 patients, 60 were school-aged and 18 were preschool-aged children. A significant difference was noticed between DVS score (p < 0.01) and NE score (p < 0.01) before and after vibroacoustic therapy in school-aged children. No significant correlation was observed between the success of vibroacoustic therapy and factors such as enuresis type (primary/secondary), applied form of pharmacologic therapy, baseline DVS and NE score, and the presence of a positive family history and expressed through percentage of decrease in DVS and NE scores in school-aged children. Conclusion: The results of the present study showed the positive effect of the vibroacoustic therapy in school-aged children with functional voiding disorders. It is, however, necessary to conduct further prospective studies in order to confirm its effectiveness and determine its long-term results. Keywords: Child; Enuresis; Urinary bladder.